2019
DOI: 10.1111/disa.12352
|View full text |Cite
|
Sign up to set email alerts
|

Disaster journalism: fostering citizen and community disaster mitigation, preparedness, response, recovery, and resilience across the disaster cycle

Abstract: Natural and human‐caused disasters pose a significant risk to the health and well‐being of people. Journalists and news organisations can fulfil multiple roles related to disasters, ranging from providing warnings, assessing disaster mitigation and preparedness, and reporting on what occurs, to aiding long‐term recovery and fostering disaster resilience. This paper considers these possible functions of disaster journalism and draws on semi‐structured interviews with 24 journalists in the United States to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…However, in some cases, no specific disaster contexts were chosen. Some explored the use of social media for post-disaster emergency response through in-depth interviews and surveys [30][31][32][33] and others explored the use of social media for post-disaster temporary memorializing, journalists' use of social media, or approaches to bridging the gap between emergency managers and the public [34][35][36]. Finally, other studies -most notably the ones conducted by Wukich and Mergel [37], and Dutt et al [38] -looked at more than one disaster event.…”
Section: Technical Note Organization and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in some cases, no specific disaster contexts were chosen. Some explored the use of social media for post-disaster emergency response through in-depth interviews and surveys [30][31][32][33] and others explored the use of social media for post-disaster temporary memorializing, journalists' use of social media, or approaches to bridging the gap between emergency managers and the public [34][35][36]. Finally, other studies -most notably the ones conducted by Wukich and Mergel [37], and Dutt et al [38] -looked at more than one disaster event.…”
Section: Technical Note Organization and Methodsmentioning
confidence: 99%
“…Research also suggests that social media can foster relationships between affected communities and journalists during recovery. Research has found that U.S. journalists could act as facilitators between recovering communities and the agencies tasked with overseeing that process, as well as information providers to recovery entities on existing community needs and resources [35].…”
Section: Social Media For Post-disaster Relationship Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The community preparedness framework is needed as a standard to find out what needs to be prepared before, a moment, and immediately after a disaster occurs (Hidayati, 2008). This framework is used as a tool to assess the extent of community preparedness in an area (Houston et al, 2019). This framework has been based on the LIPI-UNESCO / ISDR standard in 2006, which includes knowledge and attitudes, policies, emergency response plans, disaster warning systems, and resource mobilization (Paramesti, 2011).…”
Section: Community Preparednessmentioning
confidence: 99%
“…Social functioning will develop if individuals are satisfied with roles in their lives, and are satisfied with relationships with others. In this case, the government has not yet played its role optimally, and this has an impact on community preparedness especially concerning information disclosure (Appleby-Arnold et al, 2018;Houston et al, 2019;Raharjo, 2013). Acceptance of public outreach and education from the government is one obstacle besides the accessibility factor in preparedness.…”
Section: Mobilization Of Resourcesmentioning
confidence: 99%